Validitas Empiris Model Valuasi Ohlson (1995) - Anggit Esti Irawati; Erna Fitri Komariyah (The Indonesian Journal of Accounting Research, 2013)
This research tests the empirical validity of Ohlson (1995) valuation model by evaluating whether its valuation results explain market prices. Unlike previous researches that violated the model's assumption, which led to questionable conclusion, this research satisfies its assumptions regarding the calculation of abnormal earnings, which involves the clean surplus relation and risk-free discount rate, and in the attributes of the model's parameters that should be unique for each firm. The reexamination of the validity of the model is important considering the fact that the model has been utilized as a theoretical basis in determining market-based accounting research variables, such as risk and cost of capital. The result of this research indicates that the valuation results of Ohlson (1995) model are positively associated with market prices. The valuation error of the model is less than the valuation error of book value, suggesting that the Ohlson (1995) model is better than book value in explaining price. Nevertheless, the valuation result is still significantly less that market price, the difference of which might be a result of errors in estimating the model's parameters or even a misspecification in the model. The differences between the model's valuation result and price, however, implies a still open opportunity to conduct fundamental accounting researches.